Comparative analysis of the transcriptome and proteome during mouse placental development - Abdulghani, M; Song, G; Kaur, H; Walley, JW; Tuteja, G (American Chemical Society, 2019)
The condition of the placenta is a determinant of the short- and long-term health of the mother and the fetus. However, critical processes occurring in early placental development, such as trophoblast invasion and establishment of placental metabolism, remain poorly understood. To gain a better understanding of the genes involved in regulating these processes, we utilized a multiomics approach, incorporating transcriptome, proteome, and phosphoproteome data generated from mouse placental tissue collected at two critical developmental time points. We found that incorporating information from both the transcriptome and proteome identifies genes associated with time point-specific biological processes, unlike using the proteome alone. We further inferred genes upregulated on the basis of the proteome data but not the transcriptome data at each time point, leading us to identify 27 genes that we predict to have a role in trophoblast migration or placental metabolism. Finally, using the phosphoproteome data set, we discovered novel phosphosites that may play crucial roles in the regulation of placental transcription factors. By generating the largest proteome and phosphoproteome data sets in the developing placenta, and integrating transcriptome analysis, we uncovered novel aspects of placental gene regulation.